Cloud Manufacturing: state of the art and evaluation of the BaSyx project - Videla Helal, Matías Emiliano (2022)
The emergence of new technologies such as the Internet of Things (IoT) and Cloud Computing hasstrongly boosted the manufacturing industry, opening the doors to a much broader world ofpossibilities and starting what many consider to be the Fourth Industrial Revolution. In this context iswhere the manufacturing paradigm of Cloud Manufacturing (CMfg) emerges, with the goal to connectmanufacturing processes through the Cloud in such a way that it allows different organizations tocooperate and to offer services to customers that could not be possible by their own independently. Asystematic review of the literature was carried out in order to determine the main characteristics andfunctionalities that a CMfg system should provide as well as the main current lines of research in thisregard. Then, we developed a prototype CMfg system based on the open source middleware EclipseBaSyx, a software development kit for CMfg systems. The developed prototype consists of a webinterface module that allows different users to create new machines and to insert job orders from thecustomers, and a server logic module that is responsible for accepting jobs, dividing them intosubtasks and distributing them among the different machines that work independently from eachother. The web module is composed by three main sub-modules: 1) a scheduler to control anddistribute the orders among the different machines of the system; 2) a verifier, which is in charge ofmonitoring the state of the machines in the real time, collecting a large amount of information fromthem and notifying the scheduler in case of failures or when they need special attention; and 3) aBaSyx module that is in charge of the creation of the Digital Twins. Finally, several numericalexperiments were carried out to show the potential of BaSyx for leveraging different productionplanning and operations management problems that may arise under Cloud Manufacturingenvironments.